Improving Ecological Intelligence of Students Through The Utilization of Inorganic Waste in Making Flipchart as a Learning Media of Social Science - Azizah, Nur Rohiimatullah (International Journal Pedagogy of Social Studies, 2018)
Environmental disrespectful behavior such as the habit of littering, indifferent about the consumption of the environmentally friendly products, then the lack of knowledge of students about environment, also low ability of students in utilizing waste reflect that the ecological intelligence of class viii-b smpn 3 lembang is still lacking. therefore it is necessary to take ways to improve the ecological intelligence of students. the efforts made for that is by utilizing inorganic waste in making flipchart as a learning media of social science. the expected objective of the research is improving the ecological intelligence of students in utilizing inorganic waste by describing started from planning, implementation, constraints and result of the improvement of the ecological intelligence of students. the classroom action research uses model of elliot. the result of the research, first, the planning process is conducted to determine sk/kd, preparing rpp includes applying the flipchart media and preparing research instrument. second, the implementation process is implementing learning aligned with the planning of the research. third, the constraints in the research is, the students are puzzled yet to determine the theme of the flipchart which is made constraints, furthermore, make students consciously keeping the environment around them. fourth, the result in the research shows the increasing in each cycle. cycle i ecological intelligence of students in utilizing inorganic waste reached the category of â€œenoughâ€ that is 66.6%. cycle ii reached the â€œgoodâ€ category that is 80.3%, and cycle iii reached the â€œgoodâ€ category that is 82.8%. therefore it can be concluded that the utilization of inorganic waste made as a media of learning in the form of flipchart includes including planning, implementation, and constraints and results obtained could improve the ecological intelligence of students.Â